Adopting EFQM Excellence Model in Educational Institutions for Long-term Quality Management - Lateh, Musammil (JURNAL AL-TANZIM, 2024)
This research is motivated by creating a sustainable educational environment aligned with a long-term vision. This study aims to analyze the implementation of the EFQM model in building the quality of sustainable education in schools. The method used is a qualitative approach with a case study design, where data is obtained through in-depth interviews, observations, and documentation. Data analysis was carried out using an interactive analysis model, including data reduction, presentation, and verification. The study results indicate that implementing the EFQM model in schools strengthens leadership and strategic alignment, which play an important role in setting a long-term vision and sustainability goals. Efficient resource management ensures cost efficiency and operational sustainability. Regular performance measurement and innovative teaching approaches help create a sustainable educational environment and support the achievement of quality education. These findings are expected to provide insight into how performance measurement and innovation in teaching approaches are important in creating an efficient and quality educational environment.